Penerapan Batas Usia Perkawinan Sebagai Upaya Perlindungan Terhadap Anak - Sri Murni; Sri Purwaningsih (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2022)
Marriage at the age of children has a negative impact on children's growth and development and causes non-fulfillment of children's basic rights. The purpose of this study is to analyze how the application of the age limit for marriage as an effort to protect children. Research method, using normative juridical research type, the type of data used is secondary data and supported by primary data, analysis method using qualitative discrete. The results of the study, Government policy in setting the minimum marriage limit for women from 16 years to 19 (nineteen) years.as stated in Law No. 16 of 2019 has gone through a process and various considerations. This is so that both parties are ready and mature from the physical, psychic and mental sides. Under certain circumstances, the Court may grant marriage dispensation in accordance with applicable laws and regulations, namely Supreme Court Regulation No. 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation. Marriage dispensation for minors, is a study of the age limit for a person to marry, or the ideal age to enter the world of marriage. The age of marriage will affect many things on oneself and on the household to be built. The role of the courts through marriage dispensation is significant in providing protection to children. The court has the authority to allow or deny permission for a child to marry or not to marry.